“People look and ask lots of questions”: caregivers’ perceptions of healthcare provision and support for children born with cleft lip and palate - Hlongwa, Phumzile; Rispel, Laetitia C. (BioMed Central, 2018)
Background: Clefting of the lip and/or palate (CL/P) is amongst the five most common birth defects reported in South Africa. The emotional impact on parents at the birth of their new-born with CL/P could affect parent-child relationships. In light of insufficient scholarly attention parental experiences and perceptions, this study reports on caregivers’ perceptions of health service provision and support for children born with cleft lip and palate in South Africa. Methods: The study setting consisted of 11 academic hospital centres situated in six of South Africa’s nine provinces. At each of the academic centres cleft clinic, five to ten parents or caregivers were selected purposively. Participants were interviewed, using a semi-structured interview schedule that elicited socio-demographic information, explored the family experiences of having a child with CL/P, and their perceptions of care provision and support services available. The interviews were analysed using thematic content analysis. Results: Seventy-nine participants were interviewed. Their mean age was 33.3 years (range 17–68 years). The majority of the parents were black African (72%), unemployed (72%), single (67%) and with only primary school education (58%). The majority of the children were male, with a mean age of 3.8 (SD = ±4.3) years. Five broad themes emerged from the interviews: emotional experiences following the birth of a child with cleft lip and palate; reactions from family, friends or the public; the burden of care provision; health system responsiveness; and social support services. Caregivers reported feelings of shock, anxiety, and sadness, exacerbated by the burden of care provision, health system deficiencies, lack of public awareness and insufficient social support services. Conclusions: The findings have implications for the integrated management of children with cleft lip and/or palate, including information to parents, the education and training of healthcare providers, raising public awareness of birth defects, and social support.
Keywords: Cleft lip and palate; Parents; Caregivers; Healthcare; Social support; South Africa; Children; SDG-3: Good health and well-being